Migration and new information and communication technologies: romanian immigrants in Spain - Martínez, Rafael Viruela (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
Technological development in the telecommunication sector affects all human activities, including international migrations. The new information and communication tools give to recent migrations characteristics which make them different from the previous population fluxes. With these tools, the immigrants can have access to basic information on the different steps of the migration process. They also allow immediate and regular communication which diminishes the physical and affective separation from family and home. At the same time, they contribute to the appearance and consolidation of immigrant networks and associations at the arrival country, and they are very helpful for building relationships with the reception society.The recent and accelerated increase of Romanian immigration into Spain has coincided with the development of new technologies,which Romanian citizens have used to inform and mobilize their compatriots, to preserve their identity and cultural features,and to facilitate the integration process in the reception country.